2014
DOI: 10.2478/dna-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial markers for identification and phylogenetic studies in insects – A Review

Abstract: Similar morphology and high genetic diversity poses problems in phylogenetic studies of insects. To solve these problems, mitochondrial based markers have been adopted and are increasingly used as molecular markers for phylogenetic studies. Varied markers have been used for different species of insects, viz., markers for 16S r RNA, 12S r RNA, ND (1-6 genes), ATPase and control regions. Among which protein coding gene, CO-1 is found to be best because of its advantage over others whereas, AT rich region of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 75 publications
1
61
0
5
Order By: Relevance
“…Mitochondrial DNA (mtDNA) has been used extensively as DNA markers in population and evolution studies (Harrison, ; Castro et al ., ) and cytochrome c oxidase subunit I (COI) has been noted as the best among the protein coding genes in insects (De Mandal et al ., ). The complete sequence of the mitochondrial COI of Z. tau complex has a total length of 1534 bp (Yong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Mitochondrial DNA (mtDNA) has been used extensively as DNA markers in population and evolution studies (Harrison, ; Castro et al ., ) and cytochrome c oxidase subunit I (COI) has been noted as the best among the protein coding genes in insects (De Mandal et al ., ). The complete sequence of the mitochondrial COI of Z. tau complex has a total length of 1534 bp (Yong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Mitogenomes, the entire mitochondrial genome, have been widely used as a target molecule to elucidate different aspects of metazoa species evolution such as population dynamics and phylogenetic relationships 12 . Complete mitogenomes are reliable tools to be used as a molecular marker in ecological and evolutionary studies because they provide genes with different evolutionary rates such as the most conserved rRNA genes (12S and 16S), the intermediate ND1-6 genes and the fast evolving Cytochrome oxidase subunit I (COI) gene, the most used molecular marker for species identification, allowing an accurate establishment of both ancient and recent speciation events [13][14][15] . In addition, mitogenomes have a uniparental heritage, high copy number per cells and single-copy genes which facilitates DNA recovery and phylogenetic analysis [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The control region plays a role in the replication and transcription of mitogenome. Several studies have demonstrated the utilities and potential of mitochondrial PCGs (cox1 and cox2) as barcode markers in the order Lepidoptera (5). Few studies have also elucidated the comparative analysis among the domesticated and non-domesticated lepidopteran mitogenomes (6,7).…”
Section: Introductionmentioning
confidence: 99%